The convergence properties of a new type of conjugate gradient methods - Mustafa, Mamat; Mohd Rivaie, -; Abdelrhaman, Abashar (2014)
Conjugate gradient (CG) methods are widely used for solving large scale unconstrained optimization problems. Many studies have been devoted to develop and improve these methods. In this paper, we compare our new CG coefficient ( k) with the other classical formulas of CG methods under the exact line search. Numerical results have shown that our new  k performs better than these classical formulas. Our method also possesses global convergence properties.